Jembatan Transmisi Keilmuan Islam ke Eropa - M. Misbahuddin (The Pontianak State Institute of Islamic Studies, 2015)
This article attempts to unravel the role of a city drowning in a sea of history in the process of transition Islamic sciences in Europe. The analysis shows that the Sicilian town does not contribute less important than Andalusia and Granada in the transformation of science. This is because the attitude that Christian leaders built tends to differ with the leaders of Andalusia and Granada. Religious tolerance attitude and glorification of science are the mark of Christian leaders in Sicily. Therefore, although the city is no longer led by Sicilia Muslims, Islamic education remained in this prestigious Sicilia community. Theoretically, this study shows that a decision in favor of the development of the teaching of science can give back and forth, and it is not because of a problem of religion that is embraced by the authorities.